The Contribution of Village Youth Organisations in Developing Young Citizens' Civic Virtue Values - Wisnu Hatami (International Journal of Education and Humanities, 2023)
The study of young citizens is still evolving. As the largest population, young citizens need to be equipped with various values in order to become mature citizens when they grow up. One of the important values for young citizens is civic virtue. Civic virtue is related to the virtues of citizenship. So, it is very important to see the contribution of youth organisation activities that are closely related to young citizens in developing the value of civic virtue of young citizens. This research uses a case study method with a qualitative approach with resource persons from the youth organization, the village head, and the community of Dompyong Wetan village. The results showed that Karang Taruna has contributed to developing the value of civic virtue with various habits and activities developed by prioritising the value of social responsibility, participation of young citizens and also getting used to having a high commitment in advancing the village